Stakeholder perspectives on ecosystem-based management of the Antarctic krill fishery. (June 2016) - Cavanagh, Rachel D.; Hill, Simeon L.; Knowland, Cheryl A.; Grant, Susie M.
Abstract: Information about stakeholder aspirations is a fundamental requirement for ecosystem-based management, but the detail is often elusive, and debates may focus on simplistic opposing positions. This is exemplified by the Antarctic krill fishery, which, despite a current operational catch limit equivalent to just 1% of the estimated biomass and actual annual catches much lower than this, is the subject of a high-profile debate framed around ambiguous concepts such as sustainability. Q methodology was applied to explore the detailed views of representatives of three stakeholder sectors (the fishing industry, conservation-focused non-governmental organisations (NGOs), and scientists from seven countries involved in research on the krill-based ecosystem). The analysis distinguished two clear groupings, one of which included the views of all NGO participants while the other included the views of fishing industry participants and a subset of the scientists. Key differences between the groups included the priority given to different management measures, and to continued commercial fishing. However, the results also revealed considerable overlap between viewpoints. Both groups prioritised the maintenance of ecosystem health and recognised the importance of defining management objectives. Also, neither group prioritised a decrease in catch limits. This suggests that most participants in the study agree that management should improve but do not perceive a major problem in the ecosystem's ability to support current catch levels. Cooperation to identify shared management objectives based on stakeholder aspirations for the ecosystem might enhance progress, whereas polarised discussions about preferred management measures or ambiguous concepts are likely to impede progress. Highlights: Q methodology was used to explore perspectives on the Antarctic krill fishery. Analysis of the detail reveals more common purpose than the debate implies. Agreed priorities include ecosystem health and defining management objectives. Attitudes differ towards commercial operations and specific management measures. Understanding shared goals and areas of conflict enhances stakeholder engagement.